In vitro Antioxidant Activity and Stability Indicating High-performance Thin-layer Chromatographic Method for Ximenynic Acid in Santalum album Seed Extract - Shivatare, Rakesh S. (Asian Journal of Pharmaceutics (AJP), 2020)
Introduction: Due to emergent concern about the unhealthy consequences of chemicals in the health industry, the interest toward natural and herbal substances have been growing every day; though, regrettably they possess several quality control issues. In this study, the antioxidant effect of Santalum album seed extract was evaluated. Furthermore, discover effortless, accurate, responsive, and stability-indicating high-performance thin-layer chromatographic (HPTLC) assay method for the detection and quantification of ximenynic acid in S. album seed extract. Materials and Methods: Antioxidant activity was evaluated by 2, 2-diphenyl-1, 1-picrylhydrazyl (DPPH) radical scavenging method. The HPTLC method contains aluminum plates precoated with silica gel 60 F254 as a stationary phase. The mobile phase was a combination of toluene: chloroform:methanol: formic acid (2:5:0.3:0.3 v/v/v/v). Densitometric analysis of ximenynic acid was carried out in the absorbance mode at 550 nm using Camag thin-layer chromatography scanner-3. Results: Antioxidant potential was observed in DPPH scavenging assay (EC = 4.0 Â± 0.02 mg/mL) and by S. album seed extract. The HPTLC method was validated as per the ICH guidelines for specificity, precision, linearity, robustness, and accuracy. The method was established to give dense and symmetrical band for ximenynic acid at retention factor 0.45 Â± 0.02. The repeatability of the method was found to be 1.25 relative standard deviations and recovery values from 99.94 to 100.10% for ximenynic acid. Conclusion: These findings indicate that S. album seed extract may have antioxidant potential. Statistical analysis confirmed that the projected method is repeatable, selective, and accurate for estimating the content of ximenynic acid. Since the projected mobile phase successfully resolves the ximenynic acid, this HPTLC method can be useful for identification and quantitation of these phytochemicals in herbal extracts and pharmaceutical dosage form.